O slogan e suas múltiplas dimensões na publicidade - Brasil, Luciana Floriano (2009)
This work focuses on slogans and their multiple dimensions in publicity with a view to understanding their configuration, their relation with catchphrases and the way that they are used in the creation of a hegemonic speech, which reproduces social practice so as to manipulate the imaginary, consolidate the power of the product and encourage consumption. In our analysis, we chose two advertising posters of the beer companies Antarctica and Skol, photographed in July, 2008 at bars in the south of the city of São Paulo. Despite promoting the same product, these advertisements use different mechanisms to attract their target public and make for rapid identification of their brand. We use two study areas as theoretical reference. First, Social Theory of Speech - which considers language as a social component describes, analyses and interprets power structures, domination and their effect on individual conduct. Second, Rhetoric, which provides support to the analysis of slogans as part of the process of persuasion. This study borrows greatly from the ideas of Norman Fairclough (1989, 2001), who views speech as action on individuals or on society, and from research into advertising slogans carried out by Olivier Reboul (1975) and Luiz Carlos Iasbeck (2002). As to Rhetoric, it too relies on the ideas of Olivier Reboul (2004) and his contribution to the understanding of advertising language within the rhetorical sphere. We have also profited from the work of various other scholars, cited throughout this work, and whose contributions also helped shape the ensuing conclusions. In the field of Social Theory of Speech, we found that slogans are never innocent statements; they incorporate values, beliefs, power relations; all in all, they reflect a discursive and social practice. In the field of Rhetoric, we found that in spite of structural similarities, slogans show peculiarities which defy categorization as catchphrases and that the rhetorical tools used intensify meaning and leave room for multiple interpretations which go beyond the mere demonstration of creativity. After all, they are responsible for all persuasive power